Validation of the Academic Analogue of Psychological Momentum Theory on Sophomore Engineering Undergraduates for the Promotion of SDG4 Quality Education - R., Chakraborty; J., Kaur (Journal of Engineering Education Transformations, 2025)
The study validated an integrated framework of the academic analogue of the Psychological Momentum theory (PMT) in the context of Sophomore Slump phenomenon, based on the preliminary work of [9]. The sample of the study was 303 Second Year Computer Science, Mechanical, and Electronics Engineering Students under the STEM discipline at the Lovely Professional University, Phagwara, Punjab, India. The tools used for the study were the Academic Procrastination scale – short form by [33], the Engineering Self-Efficacy scale by [22], the Academic Inertia Scale by [9], and the Inspiration scale by [30]. Exploratory factor analysis and reliability analysis were conducted using SPSS Statistics software Ver 23.0 on 103 subjects of the data, and the remaining 200 sample size data was used for confirmatory factor analysis study to adapt the foreign tools in the Indian context, along with the validation of the integrative framework of the academic analogue of PMT on sophomore engineering students using structural equation modeling (SEM) through SPSS AMOS software Ver. 23.0. The overall hypothesized integrative framework of PMT in academic context for second-year engineering undergraduates under the sophomore slump phenomenon, displayed acceptable goodness of fit indices. Educational and psychometric implications of the study towards the promotion of sustainable development goal 4 of quality education under STEM discipline in India, are discussed.